2018
DOI: 10.3389/fimmu.2018.00656
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic and Therapeutic Effects of Interleukin-2 (IL-2)/Anti-IL-2 Complexes in Systemic Lupus Erythematosus-Like Chronic Graft-Versus-Host Disease

Abstract: Murine chronic graft-versus-host-disease (cGvHD) induced by injection of parental lymphocytes into F1 hybrids results in a disease similar to systemic lupus erythematosus. Here, we have used DBA/2 T cell injection into (C57BL/6 × DBA/2)F1 (BDF1) mice as a model system to test the prophylactic and therapeutic effects of interleukin-2 (IL-2)/anti-IL-2 immune complexes on the course of cGvHD. Our findings demonstrate that pretreatment with Treg inducing JES6/IL-2 complexes render BDF1 mice largely resistant to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 48 publications
4
13
3
Order By: Relevance
“…Though the cause of this contraction remains undefined, we find that prophylactic treatment of diseased mice with either IL-2C or N-803 can counteract NK-cell loss and even promote expansion of the NK-cell pool. Coupled with experiments detailing IL-2-based therapeutics in the MRL/lpr and B6 x DBA mouse models 28,29 , these data support the conclusion that therapeutic expansion of NK cells is possible in the context of lupus-like disease.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Though the cause of this contraction remains undefined, we find that prophylactic treatment of diseased mice with either IL-2C or N-803 can counteract NK-cell loss and even promote expansion of the NK-cell pool. Coupled with experiments detailing IL-2-based therapeutics in the MRL/lpr and B6 x DBA mouse models 28,29 , these data support the conclusion that therapeutic expansion of NK cells is possible in the context of lupus-like disease.…”
Section: Discussionsupporting
confidence: 60%
“…As a pre-disease treatment, each mixture was intraperitoneally injected every other day for a total of 3 injections, after which a bm12 splenocyte graft was injected the following day (see above). As a post-disease treatment, injections were administered once daily for three days beginning one month after graft injection 29 .…”
Section: Targeted Cytokine Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…And it is a highly potent antiviral cytokine with broad-spectrum immunomodulatory effects [55]. It is reported that the beginning of IL-2 function depends on B and T lymphocytes, which is one of the most important lymphoid factors regulating the immune function of the body [56]. Similarly, the function of Th2 relies on the secretion of IL-4…”
Section: Effects Of Tp On Genes Expression Of Immune-related In the Smentioning
confidence: 99%